Pelatihan Pemanfaatan Teknologi Informasi untuk Meningkatkan Efektivitas Pengajaran di SMA Cinta Kasih Medan - Andi; Ongsa Ong, Rezeki; Chandra, Randy Brilliant; Roseline (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This community service aims to enhance the competency of SMA Cinta Kasih Medan teachers in utilizing information technology (IT) to support teaching effectiveness in the digital era. The importance of IT training is emphasized given the identified initial problems of varying digital skills among teachers and minimal use of interactive media and online learning platforms. The methods employed include training, workshops, and mentoring. The implementation stages cover identifying teacher needs through surveys and interviews, developing relevant training modules (encompassing Google Classroom, interactive presentations, simple video creation, and effective utilization of online learning resources), conducting training with demonstration and direct practice methods, and continuous mentoring and evaluation. The activity was participated by 15 SMA Cinta Kasih Medan teachers with a 100% attendance rate. The main results indicate that most teachers successfully mastered the taught skills, with proficiency percentages reaching 93% for virtual classroom management and 100% for utilizing online learning resources. This training positively impacted teachers' knowledge, skills, and confidence in integrating IT, potentially increasing student engagement and diversifying teaching methods. The training successfully enhanced teachers' digital competency significantly, making it a model for sustainable educational development.